Tour guide performance and servicescape relationship in tour guiding experience at the National Park, Malaysia - Tan, Sing Ee (2013)
Numerous studies have been conducted on tour guides such as the service quality,tour guides’ roles and tourist satisfaction. However, few studies were conducted on the causal relationship of tourist satisfaction with overall tour guiding experience in the context of ecotourism. Thus, this study aims to investigate the relationships between tour guide performance, servicescape and tourists’ satisfactions in the context of guided tour in Taman Negara National Park based on an established model. Modifications were made on the model on the basis of propositions that relate tour guide performance, servicescape, tourist satisfaction with guiding service along with tourist satisfaction with servicescape. Data collection was conducted in Taman Negara National Park whereby the targeted respondents were tourists who had engaged the services of tour guide. Using convenience sampling, a total of 385 valid questionnaires were collected from the survey. ‘Statistical Package Social Sciences’(SPSS) was the tool applied for data analysis, where the correlation and multiple regression analysis verified the hypotheses. The results from the analyses support all six hypotheses, which indicated that the constructs had significant affect on overall satisfaction. Both tour guide performance and servicescape were found to have influence on tourist satisfaction with guiding service and servicescape. Then, tourist satisfaction with guiding service and servicescape were found to have strong influence on tourist satisfaction with overall tour guiding experience. Another important finding was the establishment of the newly developed attributes of tour guide performance and servicescape. On the whole, the study contributed to the present body of knowledge on tourist satisfaction with tourism services. Managerial implications were discussed based on the findings.